Biomonitoring of nurses occupationally exposed to antineoplastic drugs: the IMEPA Project - Bolognesi, Claudia; Nucci, Maria Concetta; Colacci, Anna Maria; Grilli, Sandro; Ippoliti, Flora; Mucci, Nicolina; Romano Spica, Vincenzo; Barbieri, Anna; Canitano, Nicoletta; Chiozzotto, Daniela; Di Renzo, Livia; Giordano, Elena; et al. (Epidemiologia e prevenzione, 2005)
To develop a multiple-endpoint monitoring system in order to assess and minimize long term risks in hospital nurses exposed to antiblastic drugs. Molecular epidemiology study. S. Orsola-Malpighi Hospital in Bologna, Italy: nurses exposed to antiblastic drugs. 50 exposed subjects (8 males and 42 females) and 50 unexposed individuals (8 males and 42 females) matched for age and smoking habits. Urinary markers of exposure, Heat Shock Proteins (HSPs) 27, 70, 90, 110, immunologic biomarkers in peripheral blood lymphocytes: apoptosis, cell-cycle analysis G1-S-G, typization of Natural Killer cells (NK) and receptors micronuclei; frequency in peripheral blood lymphocytes and in exfoliated buccal mucosa cells; activation ofspecific oncogenes (bax, bcl2). 19/50 subjects showed urinary antiblastic drug levels (3 subjects MTX, 11 subjects CP, 5 subjects MTX and CP). No statistically significant differences were observed in all the considered biomarkers between the exposed and control groups. This biomonitoring study doesn't evidence any early significant effect associated to the exposure to antiblastic drugs.